Tác động của chuyển đổi số, chất lượng dịch vụ đến ý định tiếp tục chọn đào tạo trực tuyến ở các trường đại học ngoài công lập - Lê Quốc, Thắng; Lê Thanh, Tiệp (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
E-learning plays an important role in Vietnam's education in the context of the COVID-19 pandemic, in addition to traditional training. E-learning programs are developed according to the development trend of digital transformation as well as have positive impacts on service quality and increase learner satisfaction. From there, the intention to choose online training is formed. The objective of the study is to evaluate the simultaneous impact of digital transformation and service quality on the intention to continue choosing online training at non-public universities. The study uses a combination of qualitative and quantitative research methods, conducting a survey with learners/students at non-public universities and collecting 362 qualified responses for analysis. The process of data analysis through SmartPLS is to evaluate the research model and test the hypothesis, thereby analyzing, researching and proposing managerial implications for the process of managing and developing online training programs at non-public universities.
Keywords: Digital transformation; Service quality; Intention to choose online training; Non-public universities